The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3892/etm.2020.9217
|View full text |Cite
|
Sign up to set email alerts
|

Use of polymyxin B in patients with renal impairment: A retrospective examination of 5 cases

Abstract: In order to provide an idea dose of polymyxin B in Chinese patients with renal impairment, the present study collected the clinical data of all patients with renal impairment who received polymyxin B therapy in the intensive care unit (ICU) of The First Affiliated Hospital of Bengbu Medical College (Bengbu, China). The clinical data of six patients treated in the ICU between February 2018 and May 2019 were retrospectively analyzed. All patients had renal impairment and were treated with polymyxin B combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The reasons underlying our unexpected observation of sensitivity of the Gram-positive Enterococcus strains to PMB under anaerobic conditions remain to be elucidated (Figure 7A). Recently, more studies suggested that polymyxins can bind to teichoic acid, which is a negatively charged compound in the OM of Gram-positive bacteria (Brown et al, 2013;Rudilla et al, 2018;Yu et al, 2020). We speculated that different degrees of teichoic acid-like production might occur in anerobic culture conditions.…”
Section: Discussionmentioning
confidence: 98%
“…The reasons underlying our unexpected observation of sensitivity of the Gram-positive Enterococcus strains to PMB under anaerobic conditions remain to be elucidated (Figure 7A). Recently, more studies suggested that polymyxins can bind to teichoic acid, which is a negatively charged compound in the OM of Gram-positive bacteria (Brown et al, 2013;Rudilla et al, 2018;Yu et al, 2020). We speculated that different degrees of teichoic acid-like production might occur in anerobic culture conditions.…”
Section: Discussionmentioning
confidence: 98%
“…There are also some studies that supported the view that the polymyxin B dose should be adjusted in renal impairment patients ( Table 1 , Entries 10–13). In 2020, Yu et al ( Yu et al, 2020 ) demonstrated that a relatively low dose of polymyxin B (a 100-mg daily dose for patients weighing between 50 and 75 kg) could control pulmonary infections in patients with renal impairment ( Table 1 , Entry 10). In 2021, Yu et al ( Yu et al, 2021 ) developed a population pharmacokinetic model of polymyxin B and Monte Carlo simulations on the basis of a retrospective study in 32 adult patients with varying renal function.…”
Section: Introductionmentioning
confidence: 99%